The Role of Emotion and Spirituality in Counselling Sessions: The Islamic Perspective - Ibrahim, Nurshahira; Ibrahim, Rasyad Afif; Mohamad, Nur Izzaty; Ismail, Yusof; Sapiee, Mohd Lokman; Sanuddin, Nurul Diyana; Mahmud, Maziah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Emotional intelligence and spiritual intelligence are a combination of constructs that are important in conducting counselling sessions. However, this implementation receives less attention from counsellors and clients. This study was conducted to assess the relationship between emotional intelligence (self-awareness, emotional regulation, self-motivation, social awareness, social skills, and emotional receptivity) and spiritual intelligence at one of the counselling agencies in Malaysia. A total of 200 counselling clients responded to the questionnaire, and SmartPLS analysis was employed to test the study's hypothesis. The results revealed some significant findings. First, a positive but insignificant relationship exists between self-awareness and spiritual intelligence. Second, a positive and significant relationship exists between emotional regulation and spiritual intelligence. Third, a positive and significant relationship exists between self-motivation and spiritual intelligence. Fourth, a positive and significant relationship exists between social awareness and spiritual intelligence. Fifth, a positive but insignificant relationship exists between social skills and spiritual intelligence. Sixth, a positive and significant relationship exists between emotional receptivity and spiritual intelligence. This study confirms that emotional intelligence is a crucial factor in the development of spiritual intelligence. The findings of this study can assist practitioners in understanding the diverse perspectives on the construction of emotional intelligence, guiding counselling sessions to help achieve and maintain the emotional well-being of clients. Nevertheless, for future research recommendations, scholars are encouraged to conduct a more comprehensive assessment of spiritual elements in relation to emotional intelligence within counselling sessions.